S92 Efficacy Of Once-daily Tiotropium Respimat® 5 µg From Five Phase Iii Trials In Adults With Symptomatic Asthma. (10th November 2014) - Price, D; Bateman, ED; Paggiaro, P; Kaplan, A; Engel, M; Schmidt, H; Moroni-Zentgraf, P; Kerstjens, HAM
Abstract : Background: Recent clinical trials have indicated that the long-acting antimuscarinic agent tiotropium, a once-daily long-acting bronchodilator, may provide benefit to patients with symptomatic asthma. We investigated primary efficacy data (lung function, risk of severe exacerbation and seven-question Asthma Control Questionnaire [ACQ-7] response) from five Phase III, randomised, double-blind, parallel-group trials that evaluated the efficacy and safety of once-daily tiotropium add-on versus placebo add-on (all tiotropium doses delivered via the Respimat ® SoftMist™ inhaler) in adults with symptomatic asthma on inhaled corticosteroid (ICS) ± long-acting β2 -agonist (LABA) maintenance therapy. Methods: Two 48-week trials of tiotropium Respimat ® 5 µg (PrimoTinA-asthma ® : NCT00776984, NCT00772538 ) in patients on high-dose ICS (≥800 µg budesonide or equivalent) + LABA; two 24-week trials of tiotropium Respimat ® 5 µg and 2.5 µg (MezzoTinA-asthma ® : NCT01172808, NCT01172821 ) in patients on moderate-dose ICS (400–800 µg budesonide or equivalent); one 12-week trial of tiotropium Respimat ® 5 µg and 2.5 µg (GraziaTinA-asthma ® : NCT01316380 ) in patients on low-dose ICS (200–400 µg budesonide or equivalent). Results: 3476 patients were treated, of whom 1128 received tiotropium Respimat ® 5 µg. Once-daily tiotropium Respimat ® 5 µg significantly improved lung function (Table ) in patients with not fully controlled asthma receiving low- to high-dose ICS. In addition, tiotropium Respimat ® 5 µg reduced the risk of severe exacerbations versus placebo (co-primary end point) in patients on high-dose ICS + LABA (hazard ratio 0.79; p = 0.0343), and there was an increase in ACQ-7 responder rate (co-primary end point) with the5 µg dose (odds ratio 1.32; p = 0.0308) compared with placebo in patients on moderate-dose ICS. Conclusion: Once-daily tiotropium Respimat ® significantly improves lung function in adult patients with symptomatic asthma receiving a range of doses of ICS, including even high-dose ICS + LABA, suggesting a potential role for this treatment as add-on to ICS in adults with symptomatic asthma.